Field relations, petrography, and age of plutonic units in the Saint John area of southern New Brunswick - White, Chris E.; Barr, Sandra M.; Bevier, Mary Lou; Deveau, Kevin A. (Atlantic Geoscience, 1990)
Intrusive rocks in the Saint John area of southern New Brunswick are divided into separate plutonic units based on field relations and rock type. The oldest intrusive rocks are granodioritic orthogneisses in the Brookville Gneiss that have an igneous crystallization age of ca. 60S Ma, and a metamorphic age of ca. 564 Ma. The metamorphic age of the orthogneiss provides an approximate maximum age for post-metamorphic plutons that range in composition from gabbro to granite. One of these, the Rockwood Park Granodiorite, has a U-Pb age of 538 ± 1 Ma. On the basis of field relations, the Rockwood Park Granodiorite occupies an intermediate position in the intrusive sequence of plutons in the Saint John area. We therefore speculate that these plutons are mainly Cambrian rather than Precambrian as has been generally assumed. RÉSUMÉ On divise les roches intrusives de la région de Saint Jean (Nouveau-Brunswick meridional) en unités plutoniques distinctes basées sur les relations de terrain et sur le type de roche. Les plus vieilles roches intrusives sont des orthogneiss granodioritiques au sein du Gneiss de Brookville, dotés d’un âge de cristallisation ignée d’environ 605 Ma et d’un âge métamorphique d’environ 564 Ma. L’âge métamorphique de l’orthogneiss foumit un âge maximal approximate pour des plutons postmétamorphiques dont la composition s’étale des gabbros aux granites. Parmi ceux-ci, la Granodiorite de Rockwood Park à un âge U-Pb de 538 ± 1 Ma. D’après les relations de terrain, la Granodiorite de Rockwood Park occupe une position intermédiaire au sein de la séquence intrusive de plutons dans la région de Saint Jean. On présume done que ces plutons sont en grande partie cambriens et non pas précambriens comme le voulait l’opinion générale. [Traduit par le journal]